Women Philosophers from Non-western Traditions: The First Four Thousand Years - Waithe, Mary Ellen; Boos Dykeman, Therese (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book presents the views of 22 women philosophers from outside the Greco-Roman and Judeo-Christian worlds. These eminent thinkers are from Mesopotamia, India, Tibet, China, Korea, Japan, Australia, America, the Philippines and Nigeria. Six philosophers, the earliest of whom predates the Greek pre-Socratics by two thousand years, lived at "the dawn of philosophy"; another six from late Antiquity through the Classical period; five more taught and wrote during the Middle Ages up to the Age of Exploration, and yet five others were active during the modern period to the mid-twentieth century. Most belonged to major philosophical traditions: Hinduism, Buddhism, Confucianism, Taoism, Zen, or Sufism. The chapters of the book describe the life and views of the philosophers, outline the fundamental features of their respective schools, and contain translations of their writings. The book is intended for scholars of philosophy and women's studies who wish to expand their knowledge ofnon-Western philosophical traditions and is ideally suited for undergraduate education. Comprehensive multilingual bibliographies of carefully documented sources offer scholars many promising resources for further research.
Part 1: The New Dawn of Philosophy -- Chapter 1. Beyond the Western Male Canon -- Chapter 2. En Hedu 'Anna of Mesopotamian Iraq, 2300 BCE -- Chapter 3. Maitreyi of India, circa 8th century BCE -- Chapter 4. Gargi Vachanavi of India, 700 BCE -- Chapter 5. Mahapajapati Gotami of India, 6th/5th centuries BCE -- Chapter 6. Khema of Great Wisdom, from India, 563-483 BCE -- Chapter 7. Meng Mu of China, circa 4th century BCE -- Part 2: Late Antiquity through the Classical Period -- Chapter 8. Sulabha of India, fluorit 400 BCE~400 CE -- Chapter 9. Ban Zhao of China, 45-116/120 BCE -- Chapter 10. Rabiya al-Adawiyah of Iraq, 714-801 -- Chapter 11. Liu Moran of China, 773-840 -- Chapter 12. Yeshe Tsogyal of Tibet, 777-876 -- Chapter 13. Hu Yin of China, fluorit 848 -- Part 3: The Middle Ages through the Age of Global Exploration -- Chapter 14 . Murasaki Shikibu of Japan, circa 978-circa 1000 -- Chapter 15. Cao Wenyi (Cao Xiyun) of China, 1039-1119 -- Chapter 16. Sun Bu'Er of China, 1124-1201 -- Chapter 17. Akkha Mahadevi of India, 1130-1150 -- Chapter 18. Empress XU/ Renxiaowen of China, 1361-1407 -- Part 4: The Modern Era -- Chapter 19. Mirabai of India, 1498-1546 -- Chapter 20. Im Yunjidang of Korea, 1721-1793 -- Chapter 21. Kang Chongildang of Korea, 1772-1832 -- Chapter 22. Nana Asma'u of Nigeria, 1793-1832/64 -- Chapter 23. Kim Iryop of Korea, 1896-1971.
Keywords: Philosophy -- History; Religion -- Philosophy; Feminist theology; Philosophy, Modern; History of Philosophy; Philosophy of Religion; Feminist Theology; Philosophical Traditions